Design and Simulation of a Pedal Operated Hacksaw Machine. - Amanya, John Jackin (Kabale University, 2024)
This study presented the design and simulation of a pedal-operated hacksaw, aimed at providing an efficient, eco-friendly, and cost-effective alternative to conventional motorized cutting tools. The pedal-powered system converts human mechanical energy into the necessary reciprocating motion for cutting materials such as metal, wood, and plastic. The design comprises a flywheel mechanism connected to a pedal, which stores kinetic energy and provides a smooth, continuous cutting action. This system is particularly suitable for small-scale workshops or areas without access to electricity, offering an energy-efficient and portable solution. Simulation of the pedal-operated hacksaw is conducted using CAD software, evaluating parameters such as force transmission, cutting speed, and efficiency. The results show that the pedal-operated hacksaw can achieve satisfactory cutting performance with minimal user effort, making it a viable tool for sustainable and low-energy applications.